Efficacy of OPD based rigid sigmoidoscopy in diagnosing the patients with bleeding per rectum - Parmar, Hardik; R., Arun; Chauhan, Sahdevsinh; Sutaria, Akshay (International Surgery Journal, 2018)
Background: The aim of study was to evaluate the patients with bleeding per rectum by rigid sigmoidoscopy and to know the various causes of bleeding per rectum in our OPD population and to select the best approach to treat the underlying pathology. Methods: A total 63 patients with bleeding per rectum in whom cause could not be ascertained by routine methods like proctoscopy were considered from outpatient department form January 2017 to June 2018 for the study. Out of 63 patients, rigid sigmoidoscopy done in 31 patients and results were documented. All 31 patients were undergone for complete clinical examination and rigid sigmoidoscopic examination in the surgical OPD and routine blood, urine and stool investigations were also done. Results: Out of 31 cases in which sigmoidoscopic examination has been done, definitive source of bleeding is identified in 22 cases (70.97%) and in 9 cases (29.03%), the source of bleeding could not be detected by rigid sigmoidoscope. Conclusions: Rigid sigmoidoscopy has a very high diagnostic yield (approximately 71% in this study) in patients with bleeding per rectum which could not be detected by routine ano proctoscopy. Hence rigid sigmoidoscopy would be recommended in the workup of patients presenting with bleeding per rectum and it also serves an equally important function in excluding serious colonic lesions like malignancy and enables us to reassure the patient.